ARGUMEN KEPEMILIKAN LUBUK LARANGAN DALAM PERSPEKTIF FIKIH MUAMALAH - Juliana Nasution; M Marliyah; Muhammad Idris Nst (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
Fish in the river are mubahah goods that do not belong to anyone so that everyone can have them perfectly (milk at-tamm) by hunting them (ishthiyad). However, in the lubuk larangan case, local villagers forbade people from anywhere to hunt fish at that location, with any fishing gear, for a certain period. They also release fish seeds there and then ask for some payment when harvesting the forbidden river for those who want to hunt fish. This article aims to describe the problems in the lubuk larangan case related to the practice of muamalah jurisprudence using qualitative methods with a fiqh-empirical approach. The results invite us to discuss how the fiqh of muamalah reviews the prohibition on hunting fish in the lubuk larangan area, the release of fish seeds in the prohibition area and their ownership status, and the transaction costs of fish hunting in the lubuk larangan area.